The value of intellectual structural imbalance in the differentiation of autism spectrum disorder and attention deficit hyperactivity disorder - Zhang, Dan-Yang; Wei, Qiu-Hong; Hu, Bin-Yue; Ai, Dan; Zhang, Yu; Ding, Yuan; Yang, Ting; Chen, Jie; Chen, Li; Wu, Yuan; Chen, Hong-Yu; Xiang, Xue-Li; et al. (Frontiers in Psychiatry, 2025)
BackgroundThe study delves into the intricate task of differentiating intellectual structures among children diagnosed with the high-functioning Autism Spectrum Disorder (HF-ASD), Attention Deficit Hyperactivity Disorder (ADHD), or comorbidity (ASD+ADHD), aiming to assist in their clinical differentiation, with the goal of refining clinical diagnoses and developing targeted therapeutic interventions.MethodsThe study included 200 outpatients aged 6.5–13.0 years (total Intelligence Quotient (IQ) 70–130) at the Children’s Hospital of Chongqing Medical University, and categorized into HF-ASD (n=91), ADHD (n=47), and comorbidity ASD+ADHD (n=62) groups. We utilized the Chinese Wechsler Intelligence Scale for Children (C-WISC) as the primary assessment tool, supplemented by additional diagnostic measures. Besides, we used SPSS 25.0 to assess the subtest scores and differences.ResultsThe comorbidity group had lower total IQ than the other two groups (p<0.001). The verbal IQ(VIQ) were lower than the performance IQ(PIQ) in HF-ASD (p=0.017) and comorbidity (p=0.007) groups. They also scored higher on perceptual organization subtests particularly in Block Design and Object Assembly than the ADHD group. The ADHD group showed higher VIQ than PIQ (p=0.020). The ADHD group’s scores for working memory subtests were lower than in the HF-ASD group. The respective peak scores for the HF-ASD and comorbidity groups were in Block Design (45%,43%) and Object Assembly (30%,37%) and valleys in Picture Completion (52%,24%), Information (HF-ASD 24%), and Arithmetic (comorbidity 42%).ConclusionThe peak-valley difference in the ADHD group ( 2 standard deviations) was smaller than in the HF-ASD and comorbidity groups ( 3 standard deviations), and this characteristic could help differentiate between HF-ASD, ADHD, and both together.